Losses of runaway electrons in MHD-active plasmas of the COMPASS tokamak. (11th May 2017) - Ficker, O.; Mlynar, J.; Vlainic, M.; Cerovsky, J.; Urban, J.; Vondracek, P.; Weinzettl, V.; Macusova, E.; Decker, J.; Gospodarczyk, M.; Martin, P.; Nardon, E.; et al.
Abstract: The significant role of magnetic perturbations in mitigation and losses of runaway electrons (REs) was documented in dedicated experimental studies of RE at the COMPASS tokamak. REs in COMPASS are produced both in low density quiescent discharges and in disruptions triggered by massive gas injection (MGI). The role of the RE seed produced in the beginning of the discharge on the subsequent RE population proved significant. Modulation of the RE losses by MHD instabilities was observed at several characteristic frequencies, as well as by magnetic field oscillations related to power supplies. Magnetic islands seem to suppress the losses as the HXR signal is low and coherent with the island rotation frequency. Moreover, periods of increased losses of REs observed in the current quench (CQ) and early RE beam plateau phase of the MGI disruptions seem to be linked to the bursts of magnetic perturbation, and to the observation of filaments in the fast visible camera images.